Comparative Study on Digitization of Prepaid Recharges Using IVR and M-Commerce - Singh , Tarandeep (Gyan Management Journal, 2020)
Interactive Voice Response (IVR) systems play an important role in collecting and disseminating information in developing regions. Recently, researchers have used IVR technology to build voice forums, in which callers leave messages that can be heard over the Internet and over the phone. However, despite their appeal, voice forums remain difficult to set up, and difficult to scale due to the overhead of moderating content and the cost of phone calls. Internet technology is regarded as the third wave of revolution after agricultural and industrial revolution. After phone technology is heralding the era of mobile in India. The growth of Mobile is phenomenal compared to previous deliver channels. It took approximately more than twenty years for Mobile to become popular for online services. More so, with India all set to emerge as the second largest mobile subscriber base in the world after China, the telecom operators are raring to use this medium to offer online services including fund transfers to all sorts of people. Mobile can be categorized as the latest advancement in digitization. The paper describes the rapid growth and development of payment systems and how there has been a slow shift from IVR e-payment systems to m-payment systems. The key mobile payment systems described in the paper includes but not limited to, the m-Paisa, Airtel money, ICICI pocket etc. The business models described in the paper have been analyzed by considering a few key factors and analysis results depicted that the biggest challenge of deploying mobile payment systems is initiated by uncertainties in the environment.
Keywords: Teacher Effectiveness; Quality of Teaching; Covid-19 Pandemic; Virtual Classroom.